Peripheral inflammatory markers indicate microstructural damage within periventricular white matter hyperintensities in Alzheimer's disease: A preliminary report - Swardfager, Walter (Alzheimers Dement (Amst), 2017)
INTRODUCTION: White matter hyperintensities (WMH) presumed to reflect cerebral small vessel disease and increased peripheral inflammatory markers are found commonly in Alzheimer's disease (AD), but their interrelationships remain unclear. METHODS: Inflammatory markers were assayed in 54 elderly participants (n = 16 with AD). Periventricular WMH were delineated from T1, T2/proton density, and fluid-attenuated magnetic resonance imaging using semiautomated fuzzy lesion extraction and coregistered with maps of fractional anisotropy (FA), a measure of microstructural integrity assessed using diffusion tensor imaging. RESULTS: Mean FA within periventricular WMH was associated with an inflammatory factor consisting of interleukin (IL)-1β, tumor necrosis factor, IL-10, IL-21, and IL-23 in patients with AD (ρ = −0.703, P = .002) but not in healthy elderly (ρ = 0.217, P = .190). Inflammation was associated with greater FA in deep WMH in healthy elderly (ρ = 0.425, P = .008) but not in patients with AD (ρ = 0.174, P = .520). DISCUSSION: Peripheral inflammatory markers may be differentially related to microstructural characteristics within the white matter affected by cerebral small vessel disease in elders with and without AD.